Last stand on the ocean shore : an unofficial Minecrafter's adventure - Cheverton, Mark (Cheverton, Mark. Mystery of Herobrine, 2015)
Herobrine is rallying all the monsters of Minecraft to one server in hopes of eliminating Gameknight999 and his friends once and for all. They destroy every village they find, threatening to continue until the User-that-is-not-a-user surrenders. Gameknight has just two things, the Oracle's command to seek out the lost ocean monument and an impenetrable riddle: "Look to the lowliest and most insignificant of creatures, for that is where your salvation will lie."